Studi Pendahuluan: Pengembangan Instrumen Penilaian Literasi Digital dan Keterampilan Proses Sains pada Materi Pesawat Sederhana - Husna, Sri Muslimatul; Darmaji; Kurniawan, Dwi Agus (Jurnal IKA, 2023)
This study aims to find out whether science teachers have used digital literacy assessment instruments and science process skills on simple machine material and to know whether students have assessed digital literacy abilities and science process skills on simple machine material. The type of research used is descriptive qualitative research. The sample used in this study was one of the eighth grade science teachers and 5 eighth grade students at SMPN 7 Muaro Jambi. The research instrument used was an interview sheet, with a semi-structured interview type. The data analysis used is qualitative data analysis using Miles and Huberman. The results of this study are that teachers have not used digital literacy assessment instruments and science process skills on simple plane material. Therefore, an instrument for assessing digital literacy skills and science process skills in simple machine materials is needed so that students' digital literacy abilities and science process skills in simple machine material can be measured properly. From the results of this study it can be interpreted that the instruments for assessing digital literacy and science process skills in simple plane material have not been used by science teachers at SMPN 7 Muaro Jambi.